دراسة مؤشرات النضج الجنسي, كمية وإنتاجية البيض عند الجيل الأول (F1) المنتخب من الدجاج البلدي السوري في البيئة الساحلية - حميشة محسن; جلنكريان بيرنا (Latakia University Journal -Biological Sciences Series, 2019)
درست مؤشرات النضج الجنسي وكمية وإنتاجية البيض خلال 150 يوماً عند 163 دجاجة بلدية محلية تنتمي إلى الجيل الأول F1 المنتخب من قطيع أولي. أظهرت نتائج البحث أن عمر النضج الجنسي بلغ 202 يوماً متساوياً بذلك مع السلالة البلدية المصرية (فيومي) 201 يوماً وأكثر بحوالي 82 يوماً مقارنة بالليغهورن الأبيض (120 يوماً). كما بلغت كمية البيض خلال الفترة المدروسة 81,1 بيضة والمتوسط الشهري 16,22 بيضة عند كامل قطيع التجربة، بينما بلغت 91,07 بيضة بمتوسط 18,21 بيضة عند الدجاجات المنتخبة لإنتاج F2. بلغت إنتاجية البيض عند قطيع التجربة 0,54 بيضة/ دجاجة/ يوم وكنسبة مئوية فإن متوسط الإنتاجية للبيض بلغت 54%. تفوقت هذه المعطيات على مثيلاتها عند بعض السلالات المحلية البلدية لبعض الدول، وبدت متواضعة جداً مقارنة بالسلالات والهجن العالمية المحسنة, وهذا ما يبرر إخضاع الدجاج البلدي السوري لبرامج تربية وتحسين جادة بهدف رفع مؤشراته الإنتاجية. The sexual maturity and egg quantity and productivity of 163 local hens of first generation of primary flock were studied for 150 days. The research results indicated that the age of sexual maturity in this case was 202 days, close to that of the Egyption local breed (Fayoumi), which was 201 days and about 82 days older than the white Leghorn (120 days). The egg quantity production achieved 81,1 eggs and the monthly average was 16,22 eggs. For the hens selected to produce F2, egg quantity production was 91,07 eggs with a monthly average of 18,21 eggs. For the studied flock, the egg productivity was 0,54 egg/hen/day and as percentage, the average of egg production was 54%. These figures excelled those of some local breeds in the other countries, which they were very modest compared with the international improved breeds and hybrids. Therefore, it is necessary to apply serious programs to raise and improve the Syrian local chicken in order to improve the indicators of its productivity.